Analysis Of Long-Wavelength Vertical-Cavity Surface-Emitting Lasers - Yap, David Fook Weng (2006)
Research and development on long-wavelength (LW) vertical-cavity surface-emitting lasers(VCSELs) have been carried out extensively due to their important role in long-haul optical communication links. Moreover, VCSELs are able to obtain high modulation bandwidth with low threshold currents compared to edge-emitting laser(EEL) devices. In this work, simulation is carried out based on the 1550-nm InGaAsP oxide-confined VCSEL structure without thermal effects and electrical parasitics. Comparison between various oxide aperture radiuses is done to study their influence on the VCSEL characteristics.